2006
DOI: 10.1002/adem.200600045
|View full text |Cite
|
Sign up to set email alerts
|

Direct Current Plasma Spraying: Diagnostics and Process Simulation

Abstract: This paper presents our current knowledge in direct current (d.c.) plasma spraying with conventional stick‐type cathode plasma torches. It deals with the experimental methods and models used to better understand and /or control the characteristics of plasma jet, particles in‐flight and at impact. The first part refers to measurements and on‐line monitoring or control. The emphasis is on (i) the effect of arc root fluctuations and electrode wear on particle treatment and coating formation; (ii) the drastic impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…On the other hand the turbulence is also the cause of the increase of the "externally entrained air and consequently a rapidly decrease of the plasma velocity" (Pfender et al, 1991). It was shown by Bisson et al (2003a) and Vardelle et al (2006), that the plasma turbulence in such PGs is the cause of a high dispersion of particle velocity (of the order of 200 m/s), as well as of particle temperature (of about 600 • C). Bisson et al (2003b) showed experimentally (with Al 2 O 3 powder) that an increase of plasma jet turbulence drastically lowered microstructure quality coating (60% higher porosity, five times higher number of unmelted particles) followed by the considerably lowered deposition efficiency, from 73% to 48%.…”
Section: Plasma Installationmentioning
confidence: 99%
“…On the other hand the turbulence is also the cause of the increase of the "externally entrained air and consequently a rapidly decrease of the plasma velocity" (Pfender et al, 1991). It was shown by Bisson et al (2003a) and Vardelle et al (2006), that the plasma turbulence in such PGs is the cause of a high dispersion of particle velocity (of the order of 200 m/s), as well as of particle temperature (of about 600 • C). Bisson et al (2003b) showed experimentally (with Al 2 O 3 powder) that an increase of plasma jet turbulence drastically lowered microstructure quality coating (60% higher porosity, five times higher number of unmelted particles) followed by the considerably lowered deposition efficiency, from 73% to 48%.…”
Section: Plasma Installationmentioning
confidence: 99%
“…The corresponding transient voltage can exhibit a restrike, take-over or mixed mode that leads to voltage fluctuations of ¡35%. 84 The frequency of voltage fluctuations, ranging between 3 and 8 kHz, depends strongly on the condition of the torch anode and its operating parameters. 83 A peak frequency at around 4 kHz is usually observed 85,86 for stick type plasma torches.…”
Section: Fuel Gas Processesmentioning
confidence: 99%